BIOLOGICAL SCIENCE AND SUBJECT: RELATIONSHIPS PROBLEMS - Komarova, O.V. (Pedagogy of Higher and Secondary Education, 2007)
The article is devoted to problem of reflection a basic science in school subject. Characteristics of biology and school knowledge and cognition are distinguished. The ties between them are established. The question about their dynamic is considered for biological courses in 7-9 forms.